Correction: Highly sensitive and wearable gas sensors consisting of chemically functionalized graphene oxide assembled on cotton yarn. Issue 37 (7th June 2018) - Kang, Min-A.; Ji, Seulgi; Kim, Seongjun; Park, Chong-Yun; Myung, Sung; Song, Wooseok; Lee, Sun Sook; Lim, Jongsun; An, Ki-Seok
Abstract : Correction for 'Highly sensitive and wearable gas sensors consisting of chemically functionalized graphene oxide assembled on cotton yarn' by Min-A. Kang et al., RSC Adv., 2018, 8, 11991–11996.